Public Innovation Support for SMEs in the Czech Republic : Focus on Cooperation Between Business and Research Organizations and Universities - Blažek, Tomáš; Stuchlíková, Zuzana, 1979-; Zeynalov, Ayaz; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the cooperation between small and medium-sized enterprises (SMEs) and research organizations in applied research and innovation. Its primary aim is to analyze the conditions that enable or hinder such cooperation, identify major barriers, and propose concrete measures for their removal. The research is grounded in two main components: a systematic review of outputs from grant-funded SME–research organization projects, and qualitative interviews with representatives of innovative SMEs. One of the study's key results is that the number of SMEs engaging in research cooperation is very limited, alongside persistent challenges in translating collaborative outputs into commercial success. Particular focus is given to the role of patents, with findings indicating that their use as a proxy for R&D activity is even more problematic than commonly recognized. Drawing on insights from the analysis, the thesis offers a set of targeted recommendations to strengthen the Czech Republic's innovation ecosystem.
Vedoucí práce: Zuzana Stuchlíková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses